The Impact of Interest in Learning on the Use of Time to Study Physics Online - A Halim; Yusrizal Yusrizal; Lilia Halim (Jurnal Penelitian Pendidikan IPA, 2022)
The development of android mobile technology has reduced student interest in learning and this will have an impact on the use of study time. Considering that this phenomenon is important to be studied in more depth, then through this study, it will be investigated the relationship between interest in learning and the use of time. The population of this study were all high school students in the city of Banda Aceh, but due to time and cost constraints, the research respondents were only taken as many as 75 students from 4 high schools in the city of Banda Aceh. Sampling using the proportional sampling method with the consideration that only classes that have implemented subject learning using online media. The data collection instrument used a questionnaire of interest and the use of learning time. Data analysis was carried out in two stages, namely descriptive and inferential analysis. Descriptive analysis was used to obtain the average data, the largest score, and the percentage. While inferential analysis is used to obtain data about the relationship between aspects of interest, aspects of time use with variables of interest and use of time. The results of data analysis showed that the correlation coefficient (r_xy = 0.68) in the high and positive category and the coefficient of determination was 46.24% at a significant level of 0.05. Inference from the results of this study, teachers need to attract students' interest in learning by choosing a model or method that has been proven to be reliable, so that students are willing to manage their study time appropriately and efficiently